2013
DOI: 10.1002/jwmg.609
|View full text |Cite
|
Sign up to set email alerts
|

A multi-scale occupancy model for the grasshopper sparrow in the Mid-Atlantic

Abstract: Identifying features of breeding habitat that influence occupancy and modeling the distribution of grassland birds is needed to direct conservation efforts to reduce population declines associated with habitat loss and fragmentation. Many recent studies on grassland bird habitat use incorporate both local and landscape attributes. However, few studies have determined the appropriate spatial scales at which to measure these relationships. We conducted roadside point counts within Delaware, USA, to determine the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 51 publications
3
14
0
Order By: Relevance
“…This result is consistent with past studies that have found impacts of landscape‐scale land cover on passerines, despite their relatively small home ranges (Knick and Rotenberry , Irvin et al. , Lee and Carroll ). A majority (79%) of the CDs that we examined had a total area of protected space that was less than 200 ha, and eight (57%) were smaller than 100 ha.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…This result is consistent with past studies that have found impacts of landscape‐scale land cover on passerines, despite their relatively small home ranges (Knick and Rotenberry , Irvin et al. , Lee and Carroll ). A majority (79%) of the CDs that we examined had a total area of protected space that was less than 200 ha, and eight (57%) were smaller than 100 ha.…”
Section: Discussionsupporting
confidence: 92%
“…It appears that CDs may function as part of a larger network of undeveloped or protected space, which renders the total area of an individual CD open space less important to many birds. This result is consistent with past studies that have found impacts of landscape-scale land cover on passerines, despite their relatively small home ranges (Knick and Rotenberry 2002, Irvin et al 2013, Lee and Carroll 2014. A majority (79%) of the CDs that we examined had a total area of protected space that was less than 200 ha, and eight (57%) were smaller than 100 ha.…”
Section: Design Factors That Influenced Bird Habitat Usesupporting
confidence: 91%
See 2 more Smart Citations
“…Occupancy models can be used to determine key variables affecting species distributions, especially in the context of grassland bird habitats (Olson et al , Nicholson and Van Manen ). Irvin et al () used multi‐scale occupancy models to show that at broad scales (5–8 km), grasshopper sparrow ( Ammodramus savannarum ) occupancy on the Delmarva Peninsula was positively associated with the amount of grassland habitat, and negatively associated with amount of development and forest. Alternatively, Hill and Diefenbach () reported that landscape‐level variables did not influence grasshopper sparrow or Henslow's sparrow ( Ammodramus henslowii ) site occupancy on reclaimed minelands; rather field shape and size were the most influential variables explaining occupancy patterns.…”
mentioning
confidence: 99%